Adaptive Multiple Testing Procedure for Clinical Trials with Urn Allocation - Hanan Hammouri; Mohammed Ali; Marwan Alquran; Areen Alquran; Ruwa Abdel Muhsen; Belal Alomari (Mathematics, 2023)
This work combines the Urn allocation and O’Brien and Fleming multiple testing procedure to compare two treatments in clinical trials in a novel way. It is shown that this approach overcomes the constraints that previously made it challenging to apply the original adaptive design to clinical trials. The method provides unique flexibility, enabling trials to be stopped early if one treatment shows it is superior without compromising the efficiency of the original multiple testing procedure in terms of type I error rate and power. Experimental data and simulated case examples are used to illustrate the efficacy and robustness of this original approach and its potential for usage in a variety of clinical settings.